Windows Mobile Game Development Building Games for the Windows Phone and Other Mobile Devices - Dawes, Adam.; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
This book will provide you with a comprehensive guide to developing games for both the Windows Mobile platform and the Windows Phone using the industry standard programming languages C# and VB .NET. You will be walked through every aspect of developing for the Windows Mobile platform$1 (Bfrom setting up your development environment for the first time to creating advanced 3D graphics. Finally, you$1 (Bll learn how you can make your applications available to others, whether distributing for free or selling online. Using extensive code samples throughout, you$1 (Bll gather all the information needed to create your own games and distribute them successfully for others to enjoy. Aimed primarily at C# developers, almost everything in the book can be used in VB .NET too. For those areas where this is not the case, workarounds are suggested so that VB .NET developers are still able to use the techniques described.s
Windows Mobile Development -- Windows Mobile and .NET -- Mastering the User Interface -- Creating Games -- GDI Graphics -- Taming the Device with the Game Engine -- Timing to Perfection -- Exploring User Input -- Sounding Out with Game Audio -- Game in Focus: GemDrops -- Common Game Components -- OpenGL ES Graphics -- New Window on the World with OpenGL ES -- Creating 2D Games with OpenGL -- The Ins and Outs of the Third Dimension -- Further OpenGL Features and Techniques -- Distributing Your Game.
Keywords: Computer science; Computer Science; Programming Techniques